2017
DOI: 10.1002/clen.201600050
|View full text |Cite
|
Sign up to set email alerts
|

Air and Soil Concentrations and Source Identification of Ambient Polychlorinated Biphenyls in the Northeastern Mediterranean Region

Abstract: Ambient air and soil samples were taken in Istanbul between November 2012 and May 2013 in order to determine polychlorinated biphenyl (PCB) concentrations. A high volume air sampler was operated to collect air samples. Soil samples were taken from top of bare land. Air PCB concentrations ranged from 201 to 705 pg m−3 with an average of 360 pg m−3. The dry weight soil PCB concentrations varied from 3.4 to 13.6 ng g−1 with an average of 8.3 ng g−1. The fate of PCBs was investigated through gas/particle partition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Air masses come over Turkey crossing Ukraine, as well as the coastal regions of Bulgaria and Romania during daytime sampling, and the Black Sea during nighttime sampling (Zemmer et al, 2012). Similar findings were reported by back-trajectory and potential source contribution function analyses for POPs measurement at different sites of Turkey (Kuzu and Saral, 2017;Yenisoy-Karakaş et al, 2012). The source areas associated with the measured ∑ 14 PBDE concentrations in İzmir included northern Africa, southern and eastern Europe (Gungormus et al, 2021).…”
supporting
confidence: 76%
“…Air masses come over Turkey crossing Ukraine, as well as the coastal regions of Bulgaria and Romania during daytime sampling, and the Black Sea during nighttime sampling (Zemmer et al, 2012). Similar findings were reported by back-trajectory and potential source contribution function analyses for POPs measurement at different sites of Turkey (Kuzu and Saral, 2017;Yenisoy-Karakaş et al, 2012). The source areas associated with the measured ∑ 14 PBDE concentrations in İzmir included northern Africa, southern and eastern Europe (Gungormus et al, 2021).…”
supporting
confidence: 76%
“…Therefore, it is not possible to investigate historical variation of OCP levels in ambient air of Istanbul. Previously, PCB levels were investigated in ambient air of Istanbul between May 2012 and May, 2013. , The mean level of ∑ 84 PCBs in summer–autumn and winter–spring was reported to be 420 pg/m 3 (88% in gas phase) and 360 pg/m 3 (86% in gas phase), respectively. In the current study, these levels were found to be 117 pg/m 3 (85% in gas phase) in summer-autumn and 15.5 pg/m 3 (74% in gas phase) in winter-spring.…”
Section: Resultsmentioning
confidence: 99%
“…450 km WNW of Istanbul), ≈10 pg m –3 for ∑ 7 PCBs in the year 2014 . Ukraine, having an intensive steel production industry and yet a significant source of PCBs release also was reported as a potential source to Istanbul for PCBs . Athens, a metropolitan city of the Eastern Mediterranean Basin, was also reported to be a source for atmospheric pollutants .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations